Antibiotic Resistance-Susceptibility Profiles of Enterococcus faecalis and Streptococcus spp. From the Human Vagina, and Genome Analysis of the Genetic Basis of Intrinsic and Acquired Resistances - Sirichoat, Auttawit; Flórez, Ana Belén; Vázquez, Lucía; Buppasiri, Pranom; Panya, Marutpong; Lulitanond, Viraphong; Mayo, Baltasar (Frontiers in Microbiology, 2020)
The spread of antibiotic resistance is a major public health concern worldwide. Commensal bacteria from the human genitourinary tract can act as reservoirs of resistance genes playing a role in their transfer to pathogens. In this study, the minimum inhibitory concentration of 16 antibiotics to 15 isolates from the human vagina, identified as Enterococcus faecalis, Streptococcus anginosus, and Streptococcus salivarius, was determined. Eight isolates were considered resistant to tetracycline, five to clindamycin and quinupristin-dalfopristin, and four to rifampicin. To investigate the presence of antimicrobial resistance genes, PCR analysis was performed in all isolates, and five were subjected to whole-genome sequencing analysis. PCR reactions identified tet(M) in all tetracycline-resistant E. faecalis isolates, while both tet(M) and tet(L) were found in tetracycline-resistant S. anginosus isolates. The tet(M) gene in E. faecalis VA02-2 was carried within an entire copy of the transposon Tn916. In S. anginosus VA01-10AN and VA01-14AN, the tet(M) and tet(L) genes were found contiguous with one another and flanked by genes encoding DNA mobilization and plasmid replication proteins. Amplification and sequencing suggested the lsaA gene to be complete in all E. faecalis isolates resistant to clindamycin and quinupristin-dalfopristin, while the gene contain mutations rendering to a non-functional LsaA in susceptible isolates. These results were subsequently confirmed by genome analysis of clindamycin and quinupristin-dalfopristin resistant and susceptible E. faecalis strains. Although a clinical breakpoint to kanamycin for S. salivarius has yet to be established, S. salivarius VA08-2AN showed an MIC to this antibiotic of 128 μg mL-1. However, genes involved in kanamycin resistance were not identified. Under the assayed conditions, neither tet(L) nor tet(M) from either E. faecalis or S. anginosus was transferred by conjugation to recipient strains of E. faecalis, Lactococcus lactis, or Lactobacillus plantarum. Nonetheless, the tet(L) gene from S. anginosus VA01-10AN was amplified by PCR, and cloned and expressed in Escherichia coli, to which it provided a resistance of 48-64 μg mL-1 to tetracycline. Our results expand the knowledge of the antibiotic resistance-susceptibility profiles of vaginal bacteria and provide the genetic basis of their intrinsic and acquired resistance.